Effect of guided imagery on anxiety of the children candidate for tonsillectomy - Mahdie Ajerloo; Sharareh Khosravi; Akram Bayati (Tehran University of Medical Sciences, 2022)
Background & Aim: Tonsillectomy is one of the most common pediatric surgeries. Preoperative anxiety in children is one of the concerns of caregivers, and its management is an important part of nursing care. The aim of this study was to investigate the effect of guided imagery on anxiety in children candidate for tonsillectomy. Methods & Materials: In this clinical trial, 70 children aged 7 to 12 years, candidates for tonsillectomy in the ENT ward of Amirkabir hospital in Arak in 2021 were divided into experimental or control groups. A demographic information form and the face anxiety scale were used to collect the data. In the control group, anxiety was assessed one hour before and 15 minutes before the surgery. In the experimental group, one hour before the operation and after completing the questionnaire, the child was asked to listen to an audio file with the hands-free for 15 minutes and visualize it in his mind. Then, the anxiety scale was completed again. Results: The mean score of anxiety before the intervention was 4.31±0.79 in the experimental group and 4.06±0.87 in the control group, which had no statistically significant difference. The mean score of anxiety after the intervention was 3.83±0.89 in the experimental group and 4.89 ± 0.90 in the control group, which showed the mean score of anxiety of children after the intervention had a statistically significant difference between the two groups (P<0.001). Conclusion: The preoperative intervention reduced preoperative anxiety in the children candidate for tonsillectomy. This intervention is an easy and safe process and can be used as an effective method. Clinical trial registry: IRCT20211008052701N1